Economists at war : how a handful of economists helped win and lose the World Wars - Bollard, Alan (Oxford : Oxford University Press, 2020)
Wartime is not just about military success. This text tells a different story - about a group of remarkable economists who used their skills to help their countries fight their battles during the Chinese-Japanese War, Second World War, and the Cold War.
This edition previously issued in print: 2019.
Includes bibliographical references and index.
Specialized.
Description based on online resource; title from home page (viewed on January 13, 2020).
Keywords: Economists -- History -- 20th century; War -- Economic aspects -- History